Dyeing Cotton and Nylon Fabrics Using Natural Dyes from Hibiscus Rosa Sinensis Leaf Extract Using Infrared Dyeing Technique - Mia Karlina; Abdurrohman (Universitas Pendidikan Mandalika, 2026)
The use of synthetic dyes in the textile industry continues to increase due to several advantages including a wide color range, high color fastness, ease of application, and relatively low cost. However, the massive use of synthetic dyes produces dye waste that is difficult to degrade naturally, potentially polluting the environment and increasing the burden on wastewater treatment. This study aims to evaluate the potential of Hibiscus rosa-sinensis leaf extract as a source of natural dyes on cotton and nylon fabrics using various types of mordants. Fresh leaves were dried and ground before being extracted using the maceration method with water as the solvent. The resulting extract was then subjected to dyeing processes using infra-red (IR) techniques. Mordanting was carried out with various mordants, namely potassium aluminum sulfate (KAl(SO₄)₂), ferrous sulfate (FeSO₄), potassium dichromate (K₂Cr₂O₇), and copper sulfate (CuSO₄) using a pre-mordanting method. Evaluation of the results was carried out based on colorimetric values ​​(K/S, L*, a*, b*, C*, and h°) and fastness tests to washing and rubbing. The results showed that the use of mordant increased the color intensity of both types of fabrics. The sample processed using mordant showed excellent color fastness to washing and rubbing.